2020
DOI: 10.1113/jp279075
|View full text |Cite
|
Sign up to set email alerts
|

Protease‐dependent excitation of nodose ganglion neurons by commensal gut bacteria

Abstract: Key pointsr The vagus nerve has been implicated in mediating behavioural effects of the gut microbiota on the central nervous system. This study examined whether the secretory products of commensal gut bacteria can modulate the excitability of vagal afferent neurons with cell bodies in nodose ganglia.r Cysteine proteases from commensal bacteria increased the excitability of vagal afferent neurons via activation of protease-activated receptor 2 and modulation of the voltage dependence of Na + conductance activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 47 publications
0
16
0
Order By: Relevance
“…Future studies are needed to start teasing apart these complexities, while also integrating the gut microbiota and metabolites into the picture. For instance, while the gut microbiota can impact EECs, it is plausible that vagal afferents themselves can be impacted by bacterial metabolites 165 .…”
Section: New Avenues For Research and Conclusionmentioning
confidence: 99%
“…Future studies are needed to start teasing apart these complexities, while also integrating the gut microbiota and metabolites into the picture. For instance, while the gut microbiota can impact EECs, it is plausible that vagal afferents themselves can be impacted by bacterial metabolites 165 .…”
Section: New Avenues For Research and Conclusionmentioning
confidence: 99%
“…Butyrate producers such as Faecalibacterium sp. have an anti-inflammatory impact on the GI tract, and F. prausnitzii is a source of serine protease that was shown to have anti-nociceptive activity by decreasing the excitability of dorsal root ganglia neurons [ 99 , 100 , 101 , 102 ]. Unknown IBS pathophysiology led to the creation of the term ‘psychobiotics’, referring to probiotics and bacterial metabolites that signal directly to the brain.…”
Section: Visceral Pain Peripheral Mechanisms Of Pain Regulation and Ibsmentioning
confidence: 99%
“…Although the mechanisms are unknown, vagal sensory neurons distinguish bacterial signals and transmit information to the brain by activating different brain nuclei and generating opposite effects on behavior. Evidence has demonstrated that ex vivo exposure of a colon section to peptidoglycan (main cell wall component of gram-positive bacteria) but not lipopolysaccharide (LPS, main cell wall component of gram-negative bacteria) evoked firing of vagal nerve endings [ 65 , 66 ] and excited vagal sensory neurons through the PAR-2 and TLR-4 receptors, respectively [ 63 ].…”
Section: Gut Microbiota-central Nervous System-immune System Interactionmentioning
confidence: 99%